2014
DOI: 10.1037/a0037078
|View full text |Cite
|
Sign up to set email alerts
|

Structural coherence and temporal stability of psychopathic personality features during emerging adulthood.

Abstract: Psychopathy is a complex personality disorder characterized by affective, interpersonal, and behavioral dimensions. Although features of psychopathy have been extended downwardly to earlier developmental periods, there is a discerning lack of studies that have focused on critically important issues such as longitudinal invariance and stability/change in these features across time. The current study examines these issues using a large sample of male adolescent offenders (N = 1,170) assessed across 7 annual time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 61 publications
6
66
1
Order By: Relevance
“…The 2‐year stability for this study was .77, the 4‐year stability was .66 (age 12), and the 9‐year stability was .50 (age 17). Additional research further supports the early stability of child psychopathy (e.g., Barry, Barry, Deming, & Lochman, ; Hawes, Mulvey, Schubert, & Pardini, ; Lynam et al., ; Salihović, Özdemir, & Kerr, ).…”
Section: Early Measurement and Temporal Stability Of Psychopathic Dimmentioning
confidence: 84%
See 1 more Smart Citation
“…The 2‐year stability for this study was .77, the 4‐year stability was .66 (age 12), and the 9‐year stability was .50 (age 17). Additional research further supports the early stability of child psychopathy (e.g., Barry, Barry, Deming, & Lochman, ; Hawes, Mulvey, Schubert, & Pardini, ; Lynam et al., ; Salihović, Özdemir, & Kerr, ).…”
Section: Early Measurement and Temporal Stability Of Psychopathic Dimmentioning
confidence: 84%
“…At the componential level, Hawes et al. () found that GM traits were related to low neuroticism and low agreeableness and higher levels of openness, conscientiousness, and extraversion. CU traits were associated with high neuroticism, low agreeableness, low conscientiousness, low extraversion, and low openness.…”
Section: Empirical Review Of External Correlatesmentioning
confidence: 99%
“…In the original study of the SQ‐48 (Carlier, Schulte‐Van Maaren, et al, ), the factor structure was based on seven correlated psychopathology subscales with one layer, which is also used in this study (see Figure S1). Before computing longitudinal measurement invariance tests, we tested the model fit with the following fit indices (Hawes, Mulvey, Schubert, & Pardini, ): CFI (acceptable when CFI > 0.95; Hu & Bentler, ), Tucker‐Lewis Index (acceptable when TLI > 0.95; Hu & Bentler, ), and RMSEA (acceptable when RMSEA < 0.06; Hu & Bentler, ). Standardized mean difference (d) with 95% confidence interval (CI), adjusted for response shift, is reported (Oort, ; Del Re, ).…”
Section: Methodsmentioning
confidence: 99%
“…The YPI was designed to assess psychopathic traits in adolescence, and there is evidence that its 3-factor structure is invariant across adolescents from several ages (Pihet, Suter, Meylan, & Schmid, 2014). Importantly, several studies have supported the YPI’s factor structure (Neumann & Pardini, 2014), internal consistency and validity among young adults in their mid-20s (Campbell, Doucette, & French, 2009; Neumann & Pardini, 2014), while evidence suggests that a short version of the YPI is a suitable measure for longitudinal investigations focused on examining stability and changes in psychopathic traits during the transition into emerging adulthood (Colins & Andershed, in press ; Hawes, Mulvey, Schubert, & Pardini, 2014). Alphas for the YPI scores in the present study were: total score = 0.93; ID = 0.91; AD = 0.73; and BD = 0.82.…”
Section: Methodsmentioning
confidence: 99%